Group music sessions in a special school: A case study of a non-verbal child with autism - Theodorou, Andria (2016)
Autism Spectrum Disorder (ASD) is a lifelong developmental disorder which appears early in life. Its core symptoms are the deficits in social, communication and emotional skills. This study constitutes an action research which is modelled by a single case study of a non-verbal boy with autism. The aim is to examine the interactions of the boy during five group music sessions at a special educational setting, and to identify potential benefits of using music to treat his autistic behaviours. Mixed methods design was adopted, by combining a small-scale survey with the members of staff as participants and observations of the music sessions. The findings indicate potential increase and improvement of the child’s social, communication and emotional skills. The limitations of the study are among others, the time constraints, the researcher’s bias and the issue of transferability. Finally, further research needs to be conducted, in order to confirm these findings. In the future, authors should consider to examine whether different types of music therapy can be adopted in music education at schools.